Ethicality of Islamic banking and finance products and services: a survey of consumers’ perceptions - Sumairi, Nor Sazwana; Musa, Muhammad Adli; Ahmad, Nadzrah (Sultan Sharif Ali Islamic University (UNISSA) Brunei, 2017)
Financial ethics emphasises the importance of developing and sustaining ethics in financial transactions. The term “financial ethics” can be understood as ethics as it is applies to ethical and moral issues in finance. In the context of Islamic finance, Islamic financial institutions that are governed by the principle of the sharī‘ah, are expected to have inherently strong ethical roots such as promoting justice and void of any illegal and unethical elements. Moreover, Islamic finance is frequently associated if not equated to ethical banking. Nonetheless, critics have highlighted the failure of Islamic financial institutions to promote such values. Therefore, Islamic banking should formulate strategies to educate and offer unique products and services differentiated by underlying financial ethics to attract more consumers to subscribe to Islamic banking products and services. This paper analyses how consumer perceive the ethicality of the products and services offered by Islamic financial institutions. It seeks to express the importance of ethical finance and the need for Islamic finance to align with ethical banking. Quantitative method is employed by surveying consumer perception on the ethicality and “Islamicness” of Islamic finance products and services. The target respondents are IIUM employees who were surveyed using a structured close-ended questionnaire. The findings suggest that ethics could well be considered as a factor which encourage the public to patronize Islamic financial institutions. Thus, Islamic financial institutions must demonstrate their commitments and efforts in providing added values to customers.